CLINICAL MANIFESTATIONS OF INFECTIOUS MYOCARDITIS IN MEN AND WOMEN - V. A. Sergeeva; A. S. Shmoylova (Klinicist)
The study objective to estimate the clinical manifestations of infectious myocarditis in men compared to women in real clinical practice.Materials and methods. A retrospective analysis of medical records from 2011 to 2015 of patients with infectious myocarditis that were hospitalized in the cardiology department No. 1 “Regional Clinical Hospital”. We compared the clinical manifestations of myocarditis in men and women. Statistical data processing was carried out with StatPlus 2009 Professional package.Results. In group of men with moderate myocarditis heart disruptions was a dominated complaint (75 %) in group of women with a similar degree of severity of the disease this complaint was also a major (71 %). However women were significantly more marked hyperthermia in this subgroup compared with men (57 % in females and 25 % males (p < 0.05)). In the subgroup with severe myocarditis in both sexes equally the most common complaint was disruptions in heart; the dyspnea was significantly more often and harder identified among men compared with women (92 % vs 72 % (p < 0.05)). In the structure of cardiac arrhythmias and heart blocks different variants of extrasystoles were significantly more often in women (64 % vs 39 % (p < 0.05)), the atrial fibrillation was more typical for men (36 % vs 28 % (p > 0.05)). The conduction abnormalities were registered in group of women.Conclusions. The clinical manifestations of infectious myocarditis in men and women revealed some interesting features. Dyspnea with severe myocarditis in men is registered more often than in women, probably due to the higher rate of smoking among men, as well as the presence of chronic obstructive pulmonary disease patients in our study. At moderate myocarditis in women hyperthermia dominated compared with men. Cardiac arrhythmias in myocarditis occur with equal frequency in both men and women, the most common extrasystoles recorded in group of women, atrial fibrillation in our study was prevalent in men. Conduction abnormalities were harder and more common in women.